Wawasan Globalisasi, Revolusi Industry 4.0 dan Society 5.0 dalam Bimbingan dan Konseling - Florentina Ema Weking; Budiyanto; Evi Winingsih (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
The changing dynamics of the times, marked by three major waves: the Globalization Era, the Industrial Revolution 4.0 (IR 4.0), and Society 5.0, have created both challenges and transformative opportunities for the Guidance and Counseling (BK) profession. Globalization demands that counselors possess global insight, sensitivity to students' psychological issues (Dahlan, 2017), and the ability to integrate local wisdom. Meanwhile, the Industrial Revolution 4.0 ushered in an era of disruption (El Fiah et al., 2021), producing a multitasking digital generation prone to psychosocial problems. This requires counselors to transform into innovators and prepare students to be adaptive and develop strong character. Ultimately, Society 5.0 offers a technology-based, human- centered society (Sugiono, 2020), where counselors are required to integrate digital technology (cybercounseling) without sacrificing the humanistic essence of service. Through this literature review, it was identified that the future relevance of guidance and counseling services depends heavily on two pillars of competency: Humanist Competence, which prioritizes social justice, cross-cultural understanding, and local wisdom; and Digital Competence, which encompasses digital media proficiency and soft skills. In conclusion, the guidance and counseling profession must immediately undertake a holistic and systematic transformation to ensure that the services provided remain effective, adaptive, and capable of producing a superior generation ready to face the complexities of global and digital challenges.